PENANGANAN PANEN DAN PASCA PANEN TEMBAKAU DI KABUPATEN BOJONEGORO - Samsuri Tirtosastro; Wahyu Musholaeni (Universitas Tribhuwana Tunggadewi, 2015)
Harvest and post-harvest activities include harvesting, processing (curing) and marketing of tobacco. Bojonegoro area recorded as a centre production of Virginia tobacco from the United States since 1927 or 88 years ago. The colonial government intends to self-sufficiency in raw materials krosok fc (flue-cured) for white cigarette factory which has been established in 1917 in Semarang. The colonial government serious enough to handle the tobacco Virginia Bojonegoro between preparing the development of the tobacco regulation, establish experimental gardens, form a control system of production, harvesting, processing and marketing. Quality control system is well-organized, according to the provisions IHT (Tobacco Industry) as well as the balance of demand and supply.Tobacco development is closely linked to the development of production systems, harvesting, processing and marketing. Harvest and post-harvest management should also be included in the system. Quality and manner of presentation (grade, SNI, packaging, etc.) quality, price formation and others should be in the system. At present time, consumers, producers, and governments are not in the system but have their have own strategy, so the harvest and post-harvest management becomes inefficient